Employment Potential of Agroforestry: A Case Study from Yamunanagar, Haryana - Bisht, N.S.; Panse, Shiv S. (Indian Journal of Agroforestry, 2020)
Yamunanagar is a small town in the north eastern part of Haryana. Of late, it has emerged as one of the biggest markets of the world for the agroforestry wood in terms of the number of farmers growing trees and supplying wood to this market. Its annual turnover was more than Rs. 10,000 million during 2002-03. Its unique location provides an ideal opportunity for the marketing of wood to the farmers of Punjab, Haryana, Himachal Pradesh, U.P. and Uttarakhand where agroforestry has been adopted in a big way. The present study indicates that the wood based industries in Yamunanagar are providing employment to around one lakh people every year and multiplying it with the minimum wage rate of Rs. 104 per day shows that this sector is generating employment worth rupees 3,000 million every year.